Development of Student Worksheets based on Probing Prompting in Science Learning for Class VIII Students At SMP N 06 Bengkulu City - Junita, Dhelia; Sari, Meirita; Adisel, Adisel (Universitas Lampung, 2024)
This research aims to develop and determine the results of a feasibility test for student worksheets based on probing prompting in science learning for class VIII students at SMP N 06, Bengkulu City. The method developed in this research is (Research & Development or R&D). The research method used in this development is the research method used to produce a particular product. Research and development according to Sugiyono consists of 10 general steps, of which the researcher will limit these 10 steps to 7 steps only up to the product revision stage. The subjects in this research were 3 expert lecturers as validation, responses from 10 class VIII students and 1 science teacher at SMP N 06 Bengkulu City. Data collection techniques in this research include initial observations to determine whether or not student worksheets are needed, interviews, and teacher and student response questionnaires. The results of this research are that the percentage of language experts is 86.66% (very feasible), the results of the material expert assessment are 83.75% (very feasible) and the results of the media expert assessment are 86.66% (very feasible). Meanwhile, data from questionnaire analysis of responses from 10 students scored a percentage of 84.64% (very practical), and 1 teacher respondent had a percentage of 89.09% (very practical). From these data, it can be concluded that the student worksheets based on probing prompting in science learning for class VIII students at SMP N 06 Bengkulu City are suitable for use as learning media to support the learning process.Keywords: Student Worksheets, Probing PromptingDOI : 10.23960/jppk.v13.i1.2024.02